The Crisis in Historical Materialism - Aronowitz, S. author. aut Link
XXV, 333 p.
Keywords: In this provocative and famous book, now substantially revised and with much new material, Stanley Aronowitz lays bare the fundamental logical problems in Marxist theory with respect to nature, gender and race relations, the concept of class, and historical time. Aronowitz has written a stunning book offering an approach towards a new way of thinking about these problems, a book which will be addressed by other Marxist scholars and by students of social and cultural theory in many disciplines.